(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the clinical characteristics of depressive disorders in adolescents and some related factors at the Vietnam National Children’s Hospital. Subject and research methods: 42 adolescents diagnosed with depressive episodes according to ICD-10 criteria came for examination and inpatient treatment at the Department of Adolescent Medicine, Vietnam National Children’s Hospital since February 2020 to September 2023. Results: The early adolescent group accounted for the majority (57.1%). Females are more common than males and the female/male ratio is 2.2/1. The majority of patients have an introverted personality (61.9%). Most patients have psychological trauma (71.4%), mainly in the school environment and family environment. The relationship between patients and parents is harmonious in 45.2% and in conflict in 54.8%. The level of depression is mainly moderate and severe (35.7% and 50%). The main symptoms include depressed mood, decreased energy, and decreased interest and pleasure, all accounting for over 85% and with no difference between the two sexes (p>0.05). Common symptoms account for over 50% and there is no statistically significant difference between the two sexes (p>0.05). Conclusion: The number of female patients got diagnosed is more often than the number of male patients. Most cases involve psychological trauma. Common clinical symptoms are: depressed mood, decreased energy and decreased interest and pleasure. Gender, personality, gender and living area are statistically significant factors related to depression.